EXPLORING THE USE OF BLENDED PBL IN GEOGRAPHY FOR ENHANCING STUDENTS’ ANALYTICAL THINKING IN THE “NEW NORMAL” CONDITION - Riyo Rosi Meisandy; Sumarmi Sumarmi; Dwiyono Hari Utomo (Universitas Sebelas Maret (UNS), 2021)
This study aims to explore a PBL model combined with the Edmodo platform on students' analytical thinking skills during a pandemic. This study used a quasi-experimental design with a control and experimental group. Participants in this study were students of class XI at SMAN 1 Suboh Situbondo, each class consisting of 15 students. Data collection was carried out after the application of the PBL model with blended learning assisted by Edmodo platform. Data obtained from the results of the pretest-posttest in control and experimental class with analytical thinking skills questions. Data analysis was carried out on the gainscore of students' analytical thinking skills with the help of SPSS 24 for Windows. The results showed that the gainscore in the experimental class was higher than the control class. Gainscore in the experimental class is 22.66 while in the control class is 14.66, thus there is a difference of 8 points. The results of data analysis in this research indicate the sig value of the independent sample t-test is 0.018 <0.05. This means that there is an effect of the implementation of PBL with the Edmodo platform on students' analytical thinking skills during the new normal condition.